Diet quality limits summer growth of field vole populations - Forbes, Kristian M; Stuart, Peter; Mappes, Tapio; Hoset, Katrine S; Henttonen, Heikki; Huitu, Otso (PloS one, 2014)
Marked variation occurs in both seasonal and multiannual population density peaks of northern European small mammal species, including voles. The availability of dietary proteins is a key factor limiting the population growth of herbivore species. The objective of this study is to investigate the degree to which protein availability influences the growth of increasing vole populations. We hypothesise that the summer growth of folivorous vole populations is positively associated with dietary protein availability. A field experiment was conducted over a summer reproductive period in 18 vegetated enclosures. Populations of field voles (Microtus agrestis) were randomised amongst three treatment groups: 1) food supplementation with ad libitum high protein (30% dry weight) pellets, 2) food supplementation with ad libitum low protein (1% dry weight; both supplemented foods had equivalent energy content) pellets, and 3) control (no food supplementation), n = 6 per treatment. Vole density, survival, demographic attributes and condition indicators were monitored with live-trapping and blood sampling. Highest final vole densities were attained in populations that received high protein supplementation and lowest in low protein populations. Control populations displayed intermediate densities. The survival rate of voles was similar in all treatment groups. The proportion of females, and of those that were pregnant or lactating, was highest in the high protein supplemented populations. This suggests that variation in reproductive, rather than survival rates of voles, accounted for density differences between the treatment groups. We found no clear association between population demography and individual physiological condition. Our results demonstrate that dietary protein availability limits vole population growth during the summer growing season. This suggests that the nutritional quality of forage may be an underestimated source of interannual variation in the density and growth rates of widely fluctuating populations of herbivorous small mammals.
Keywords: Pregnancy; Population Density; Diet; Female; hustota populace; zvířata; dietní proteiny; roční období; ženské pohlaví; Male; Arvicolinae; dieta; Seasons; těhotenství; potravní doplňky; Dietary Supplements; Animals; mužské pohlaví; Dietary Proteins